Kingdom of children : culture and controversy in the homeschooling movement - Stevens, Mitchell L. (Princeton studies in cultural sociology., 2001)
More than one million American children are schooled by their parents. As their ranks grow, home schoolers are making headlines by winning national spelling bees and excelling at elite universities. The few studies conducted suggest that homeschooled children are academically successful and remarkably well socialized. Yet we still know little about this alternative to one of society's most fundamental institutions. Beyond a vague notion of children reading around the kitchen table, we don't know what home schooling looks like from the inside. Sociologist Mitchell Stevens goes behind the scenes.